Amylin deposition activates HIF1α and 6-phosphofructo-2-kinase/fructose-2, 6-biphosphatase 3 (PFKFB3) signaling in failing hearts of non-human primates - Miao Liu (Nature Portfolio, 2021)
By analyzing tissue from non-human primates with or without heart failure and in vitro methods, Liu et al. demonstrate that amylin deposition in heart failure contributes to cardiac dysfunction via activation of HIF1α and PFKFB3 signaling. Their study demonstrates the pathological role of amylin and establishes it as a target for heart disease patients.